Capacitation induces changes in metabolic pathways supporting motility of epididymal and ejaculated sperm - Balbach, Melanie; Ghanem, Lubna; Violante, Sara; Kyaw, Aye; Romarowski, Ana; Cross, Justin R.; Visconti, Pablo E.; Levin, Lonny R.; Buck, Jochen (Frontiers in Cell and Developmental Biology, 2023)
Mammalian sperm require sufficient energy to support motility and capacitation for successful fertilization. Previous studies cataloging the changes to metabolism in sperm explored ejaculated human sperm or dormant mouse sperm surgically extracted from the cauda epididymis. Due to the differences in methods of collection, it remains unclear whether any observed differences between mouse and human sperm represent species differences or reflect the distinct maturation states of the sperm under study. Here we compare the metabolic changes during capacitation of epididymal versus ejaculated mouse sperm and relate these changes to ejaculated human sperm. Using extracellular flux analysis and targeted metabolic profiling, we show that capacitation-induced changes lead to increased flux through both glycolysis and oxidative phosphorylation in mouse and human sperm. Ejaculation leads to greater flexibility in the ability to use different carbon sources. While epididymal sperm are dependent upon glucose, ejaculated mouse and human sperm gain the ability to also leverage non-glycolytic energy sources such as pyruvate and citrate.